2019
DOI: 10.1039/c9dt01882d
|View full text |Cite
|
Sign up to set email alerts
|

A dicopper(i)-dimesoionic carbene complex as a click catalyst: mechanistic implications

Abstract: A dicopper(i) complex comprising a dimesoionic carbene and an acetate-bridge is synthesized and fully characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The k obs value is lower than that of previously reported dicopper-carbene-catalyzed reaction (k obs = 0.101 min −1 ). 37 Since the 1 H NMR spectra of catalysts A−C in DMSO-d 6 showed no dissociation of triscarbene from the complex, triscarbene-coordination might be maintained during the catalytic reaction (see Figures S2−S4). Therefore, mononuclear copper−triscarbene complexes do not form dicopper species in the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The k obs value is lower than that of previously reported dicopper-carbene-catalyzed reaction (k obs = 0.101 min −1 ). 37 Since the 1 H NMR spectra of catalysts A−C in DMSO-d 6 showed no dissociation of triscarbene from the complex, triscarbene-coordination might be maintained during the catalytic reaction (see Figures S2−S4). Therefore, mononuclear copper−triscarbene complexes do not form dicopper species in the solution.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…33,34 The intra ligand distances within the triazolylidene ring are in the expected region and comparable to previously reported triazolylidene complexes. [21][22][23][24][25][26]33,34 Further information regarding the crystal structures and selected bond lengths and angles can be found in the Supporting Information, Tables S1 and S2.…”
Section: Resultsmentioning
confidence: 99%
“…17,18 Pioneering work by Sarkar and co-workers has shown that MIC-derived catalysts often exceed the catalytic potential of their NHC congeners. 19,[20][21][22][23][24][25][26] Transferring this concept to carbazolidederived mesoionic carbenes, Bertrand and Bezuidenhout reported the first CNC pincer-type MIC ligands in 2014 (Figure 2, bottom left). 27 While this ligand was capable of stabilising a rare rhodium(I)-dioxygen adduct 28 as well as a rare T-shaped gold(I) complex, 29 its synthesis is tedious and requires the use of harmful and explosive reagents such as tertbutylhypochlorite and in situ generated 3-chlorotriazenes.…”
Section: Introductionmentioning
confidence: 98%
“…The cationic dinuclear copper complex 50 + constructed from the deprotonated ligand L9 in presence of copper(I) acetate shows a prominent activity as catalyst for the CuAAC process. 24 Mechanistic studies revealed a surprising catalyst reaction order value of 0.87. As a non-integer value below 1.0 is normally due to a fast and reversible formation of an inactive complex, the authors explain this value as the result of an equilibrium of complex 50 + with an inactive dimeric species.…”
Section: Frontiermentioning
confidence: 99%